Pretreatment and Characterization of Selected Precursors for Chitin/Chitosan Production - Salisu MOHAMMED; Abdulfatai JIMOH; Abdullahi M. EVUTI; Abdulwahab GIWA; Abubakar A. IBRAHIM (FUDMA Journal of Engineering and Technology, 2025)
This study investigated the pretreatment and characterization of three locally available biological precursors-grasshopper (Schistocerca gregaria), periwinkle shell (Tympanotonus fuscatus), and snail shell (Achatina fulica)-as potential raw materials for chitin/chitosan production. Comprehensive physicochemical analyses, including proximate composition, ultimate analysis, X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS), Textual properties, and thermogravimetric analysis (TGA) were performed to assess the compositional, structural, morphological, and thermal properties of the precursors. Proximate analysis revealed moisture content ranging from 4.44 to 5.60 wt%, ash content from 9.15 to 95.90 wt%, lipid content from 0.24 to 8.58 wt%, crude protein from 2.50 to 25.00 wt%, and crude fiber from 0.57 to 20.62 wt%. XRF analysis indicated high CaO content in snail shell (92.08%) and periwinkle shell (90.89%), while grasshopper showed significantly lower CaO content (8.97%). XRD patterns confirmed aragonite crystalline form of calcium carbonate (CaCO3) in both molluscan shells and calcite-like structure in the grasshopper. FTIR spectra revealed characteristic amide peaks in grasshopper samples and prominent carbonate stretching bands in shells. BET analysis revealed surface areas ranging from 141.05 to 331.53 m²/g, characterized by mesoporous structures. SEM-EDS morphology confirmed the mineral-organic composite nature of all samples. TGA revealed two-stage thermal decomposition patterns with initial moisture loss (81-134°C) and organic matter degradation (368-387°C). The results demonstrated that grasshopper exhibits superior potential as a chitin precursor due to its higher organic content, lower mineral composition, and distinct chitin-related functional groups. However, all three precursors showed viability for chitin/chitosan production, requiring optimized demineralization, deproteinization, and deacetylation processes with varying acid and alkali concentrations tailored to their specific compositional characteristics. This research establishes a foundation for utilizing sustainable, locally-sourced biological waste materials as alternatives to conventional crustacean-based chitin production, promoting circular bioeconomy principles and addressing environmental challenges in Nigeria.